Gotham. The complete third season [videorecording (DVD)] - McKenzie, Benjamin, 1978-; Logue, Donal, 1966-; Mazouz, David, 2001- (Warner Bros. Home Entertainment, 2017)
The stakes are higher than ever as super-villains more ambitious and depraved are introduced, and a realignment of alliances shakes up the fight for power in Gotham. Season three of Gotham peels back the curtain on the infamous criminal organization known as the Court of the Owls. With the Indian Hill escapees on the loose, Jim Gordon must take matters into his own hands as a bounty hunter in Gotham. He makes it his mission to find Hugo Strange and Fish Mooney.